2012
DOI: 10.7763/ijbbb.2012.v2.114
|View full text |Cite
|
Sign up to set email alerts
|

Potential Nutritional and Medicinal Sources from Fruit Peels in Manila, Philippines

Abstract: Abstract-The environment is continually deteriorating. Biodegradable wastes increase with increasing population. The problem in wastes affect the integrity of the earth. Problems in health and nutrition are common. Finding important chemicals from fruit peels like total sugars or carbohydrates, as well as alkaloids will help address daily challenges in nutrition and health. This study aimed to determine the phytochemicals present in the peels of the selected fruits obtained from Manila, Philippines. Specifical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 6 publications
(4 reference statements)
0
4
0
Order By: Relevance
“…A total of 112 compounds have been reported from L. domesticum (excluding nutrients such as amino acids, protein, and sugars), including various classes of triterpenoids (e.g., swietenine, onoceranoid, cycloatanoid, and tetranortriterpenoid), cardenolides, steroids, sesquiterpenes, organic acids, phenolics, and volatile compounds. It was reported that the fruit peel had an abundant level of reductive substances, glycosides, organic acids, alkaloids, flavonoids, and phenolics, but it had no saponins [ 51 , 52 ]. Phytochemical screening of the bark revealed the existence of anthraquinones, alkaloids, flavonoids, coumarins, cardiac glycosides, tannins, saponins, and iridoids [ 24 ].…”
Section: Phytoconstituents Of L Domesticummentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 112 compounds have been reported from L. domesticum (excluding nutrients such as amino acids, protein, and sugars), including various classes of triterpenoids (e.g., swietenine, onoceranoid, cycloatanoid, and tetranortriterpenoid), cardenolides, steroids, sesquiterpenes, organic acids, phenolics, and volatile compounds. It was reported that the fruit peel had an abundant level of reductive substances, glycosides, organic acids, alkaloids, flavonoids, and phenolics, but it had no saponins [ 51 , 52 ]. Phytochemical screening of the bark revealed the existence of anthraquinones, alkaloids, flavonoids, coumarins, cardiac glycosides, tannins, saponins, and iridoids [ 24 ].…”
Section: Phytoconstituents Of L Domesticummentioning
confidence: 99%
“…Phytochemical screening of the bark revealed the existence of anthraquinones, alkaloids, flavonoids, coumarins, cardiac glycosides, tannins, saponins, and iridoids [ 24 ]. Further, a toxic constituent such as lansium acid (6%) was detected in the peel [ 52 , 53 ]…”
Section: Phytoconstituents Of L Domesticummentioning
confidence: 99%
“…According to Zafar et al [ 35 ], natural coagulant neutralises the particle charges and aggregates flocs through bridging mechanisms by bio-polymers such as polysaccharides which can be found naturally in fruits and vegetables. Polysaccharides are one of the carbohydrate subgroups that contain carbon, hydrogen, and oxygen [ 36 ]. Furthermore, Aziz and Sobri [ 37 ] reported that carboxyl (C=O), hydroxyl (O-H), and amino (amine or amide) grouped together with polymeric chains have the capability to enhance flocculation through bridging.…”
Section: Resultsmentioning
confidence: 99%
“…Also showed rich in tannins (Monzon, et. al., 2016) and high alkaloids (Solidum, 2012) which have larvicidal potential.…”
Section: Substitutesmentioning
confidence: 99%